Learning curve comparison of robot-assisted and laparoscopic hepaticojejunostomy: a focus on critical suturing - Liu, Jiahui; Maeda, Takuya; Shirota, Chiyoe; Tainaka, Takahisa; Sumida, Wataru; Makita, Satoshi; Gohda, Yousuke; Nakagawa, Yoichi; Takimoto, Aitaro; Guo, Yaohui; Kato, Daiki; Yasui, Akihiro; et al. (Frontiers in Pediatrics, 2025)
BackgroundRobot-assisted surgery (RS) has gained popularity due to its potential advantages over conventional laparoscopic surgery (LS). However, the specific suturing steps that benefit most from RS in terms of efficiency remain unclear. This study aimed to compare the suturing performance and learning curves of RS and LS during hepaticojejunostomy.MethodsWe retrospectively analyzed surgical videos of patients who underwent hepaticojejunostomy performed by the same surgeon between 2016 and 2023. Cases with incomplete data or conversion to open surgery were excluded. Suturing efficiency, anastomotic precision, and learning curves were evaluated using standardized metrics.ResultsA total of 33 patients were included in the final analysis (17 RS, 16 LS). The median suture time per stitch was significantly shorter in the RS group (P = 0.017). The greatest efficiency gains were observed at the second (P = 0.041) and final stitches (P = 0.041). Complication rates were comparable between the two groups (P = 0.986).ConclusionRS significantly improves efficiency at challenging suturing steps and provides a more consistent learning curve, highlighting its potential advantage for complex pediatric procedures such as hepaticojejunostomy. Future multicenter studies with larger sample sizes and longer follow-up are needed to validate these results and explore long-term outcomes.